The struggle for Pakistan : a Muslim homeland and global politics - Jalal, Ayesha (The Belknap Press of Harvard University Press, 2014)
In a probing biography of her native land, Ayesha Jalal provides a unique insider's assessment of how the nuclear-armed Muslim nation of Pakistan evolved into a country besieged by military domination and militant religious extremism, and explains why its dilemmas weigh so heavily on prospects for peace in the region.